Meningkatkan Hasil Belajar Ekonomi Bisnis Siswa Melalui Penerapan Metode Project-Based Learning di SMKN 1 Bantul - Rr. Bernadeta Sri Widyastuti (Jurnal Kreatif Online, 2021)
This study aimed to improve student learning outcomes in Business Economics through the application of Project-based Learning methods. This research was classroom action research and was carried out in 2 cycles. The research was carried out in class X BDP 2 at SMK Negeri 1 Bantul from January to April 2020. The number of students involved was 36 people (27 Female and 9 Male). The instruments used in this study were project worksheets, observation sheets, and multiple-choice test questions. Data were analyzed using percentage techniques. Learning success criteria if the percentage of classical completeness is above 75%. The results showed that the percentage of classical learning completeness was 59.4% in cycle 1 and 95.0% in cycle 2. So, the application of the Project-based Learning model can improve student learning outcomes in Business Economics class X BDP 2 SMK N 1 Bantul.